Najpiękniejsze trumny świata. Ikonograficzny projekt Wydziału Archeologii Uniwersytetu Warszawskiego = The most beautiful coffins of the world. Iconographical project of the Faculty of Archaeology at the University of Warsaw - Niwiński, Andrzej (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Since 2018 the Author is preparing the database of the iconographic scenes and motifs met on the Egyptian coffins of the 21st-22nd Dynasties (XI - X century BC). These coffins belonging to the priests of Amon are characterized by a large number of figural motifs and numerous variants of these. All the elements of the decoration indicate a divine status of the deceased. The Author`s intention is to describe the causes of the enormous iconographic diversity and to indicate the role of the individual creativity of the artists producing the coffins, sometimes their ignorance, as well.
Keywords: iconography; priests of Amun; mummy; royal motifs; ancient Egyptian religion; coffins; workshops producing coffins; ikonografia; kapłani Amona; mumia; motywy królewskie; religia staroegipska; sarkofagi; warsztaty produkujące trumny; 21 Dynastia